(untitled) (Ekonomski vjesnik/Econviews - Review of Contemporary Business, Entrepreneurship and Economic Issues, 2016)
The innovation pressure for the German economy increases with globalization. Yet, is this also reflected in an increased innovation activity and creativity? The article at hand presents an opposing perspective: based on some statistical analyses that indeed show a decline of innovation in Germany and other developed countries during the past years, several lines of argument are presented to explain that development. Risks arising from globalization for the creativity and innovation potential of companies are identified in economic, business and psychological areas, and their possible impact on creativity and innovation is explained in detail. Furthermore, possible countermeasures are summarized. Keywords: Globalization, innovation, innovation management, creativity, medium-sized businesses, economic structure